1988
DOI: 10.1002/rob.4620050603
|View full text |Cite
|
Sign up to set email alerts
|

Numerical filtering for the operation of robotic manipulators through kinematically singular configurations

Abstract: The loss of independent degrees of freedom at singular configurations is an inherent characteristic of robotic manipulators. Due to the unavoidable singularity of mechanical wrists, singular configurations cannot be avoided by simply restricting the bounds of the workspace. Techniques for operating at singular configurations without inducing unacceptably high joint velocities or end effector tracking errors are presented. Extensions to the damped least-squares formulation which incorporate estimates of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(99 citation statements)
references
References 19 publications
(26 reference statements)
1
96
0
2
Order By: Relevance
“…Finally we compare the SIK method with other wellknown approaches, specifically the KMA [28], CCD [25], Jacobian Transpose [7,8], Pseudoinverse [9], DLS [10,11], DLS with SVD [12,13], SDLS [14], PIK [16,17], and the TGB method for anthropomorphic limbs [26] combined with the reconstruction methods presented here for the spine and clavicles. We call the latter TGBSIK.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally we compare the SIK method with other wellknown approaches, specifically the KMA [28], CCD [25], Jacobian Transpose [7,8], Pseudoinverse [9], DLS [10,11], DLS with SVD [12,13], SDLS [14], PIK [16,17], and the TGB method for anthropomorphic limbs [26] combined with the reconstruction methods presented here for the spine and clavicles. We call the latter TGBSIK.…”
Section: Resultsmentioning
confidence: 99%
“…Another numerical approach is that in which the nonlinear problem is linearized using the Jacobian matrix where at each iteration an update of the DoF is obtained. There are different strategies for this update like the Jacobian Transpose method [7,8], the Pseudoinverse method [9], the Damped Least-Squares (DLS) [10,11], the DLS with Single Value Decomposition (SVD) [12,13] and the Selectively Damped Least Squares (SDLS) [14]. A review on these strategies can be found in the work of Buss and Kim [14].…”
Section: Related Workmentioning
confidence: 99%
“…The value chosen for the damping factor can be a small constant [30] or other more sophisticated proposals in the literature can also be considered [31,32].…”
Section: Regularizationmentioning
confidence: 99%
“…To avoid ill-conditioning when implementing (5), we resorted to a singularity-robust pseudoinversion based on numerical filtering [22] and implemented as…”
Section: B Differential Inverse Kinematicsmentioning
confidence: 99%